Pendidikan dan Penggunaan Internet Menurunkan Kemiskinan di Banten - Latuconsina, Hudaya; Khusaini, Khusaini; Lesmana, Sri Jaya (UI Scholars Hub, 2024)
In the last decade, poverty patterns in Banten Province have tended to increase. There have been many poverty alleviation programs provided by governments at all levels that focus on education, social security, and so on. This research aims to examine the role of education, internet use, and internet access on poverty in Banten. Using static and robust panel analysis shows that education contributes significantly to poverty reduction in Banten’s districts/municipalities, as does the use of the internet for information/news and social media. On the contrary, internet access harmed on regency/municipality poverty in Banten. This research contributed to providing academic information about the importance of education in reducing poverty.